Severe Facial Wound in a White-eared Opossum (Didelphis albiventris) - Treatment with Ozone Therapy - Teodoro, Ananda Neves [UNESP]; de Quadros, Elza Alice; Rosado, Isabel Rodrigues; Lopes, Matheus Garcia; Martin, Ian; Alves, Endrigo Gabellini Leonel (Universidade Federal do Rio Grande do Sul, 2023)
Background: Ozone therapy (OT) is a type of treatment that uses ozone gas, which has high oxidizing power. OT has been utilized for various diseases and to accelerate the wound healing process and reduce inflammation. Additionally, OT is a low-cost treatment recommended for patients that can be easily restrained. There are several methods of ozone administration, including topical use through bagging, cupping, or rectal insufflation, in addition to ozonated autohemotherapy. Based on the benefits of OT and the scarcity of reports describing its effects on white-eared opossums (Didelphis albiventris), we report on the use of ozone in the treatment of a severe facial wound in a white-eared opossum. Case: An adult female white-eared opossum weighing 1.6 kg was rescued from a fire. The patient was pregnant, dehydrated, hypothermic and had an extensive burn wound in the facial region. Due to the stress of captivity and its aggressive behavior, the animal needed to be chemically restrained with dexmedetomidine and butorphanol. Following sedation, the cephalic vein was catheterized and intravenous fluid therapy with ringer lactate was started to treat dehydration. Next, enrofloxacin, meloxicam, and tramadol hydrochloride were administered. Body rewarming was performed with thermal bags. The microbial load of the wound was reduced with chlorhexidine degerming solution followed by washing with saline solution. A thin layer of silver sulfadiazine cream was applied to the wound area. Over the following days the patient was treated with OT using the cupping technique combined with ozonated sunflower oil. After the first applications there was an improvement in the appearance of the wound, which initially had a purulent aspect. After 20 days of treatment the wound showed good granulation and there were no signs of infection, and at 45 days of treatment it was completely healed. The patient was then released with her baby. Discussion: Ozone therapy was included in the patient’s treatment plan to enhance the tissue repair process in order to reintroduce the animal to the wild in the shortest possible time. The strategy was successful in improving healing and reducing tissue inflammation and infection. Ozone is known to cause the inactivation of microorganisms as a result of the oxidation of phospholipids and lipoproteins present in the cell membrane of bacteria and to interrupt viral replication. Ozone helps in the perfusion of injured tissues, contributing to the entry of humoral components, which control inflammation. Moreover, ozone contributes to increase supply of oxygen and nutrients to tissues and to stimulate increased production of fibrinogen and formation of granulation tissue. Ozone increases the enzymatic antioxidant response, while also playing a role in immunoregulation. Ozone can be used in several ways and via various methods with potential routes including intravenous, urethral, intramuscular, subcutaneous, or intra-articular, in addition to rectal and intramammary insufflation. Immunomodulatory, anti-inflammatory, analgesic, and antiseptic effects can be achieved with different doses and concentrations, which enables its application in different types of pathologies. Because of the aggressive behavior of the animal, in the current case we opted for the cupping technique combined with ozonated oil, both techniques which can be administered easily with only physical restraint of the patient. Cupping allows for the provision of a higher concentration of ozone gas locally whereas the ozonated oil maintains the effect of the gas for slightly longer, enhancing its effect and promoting tissue repair. The present report showed that OT is an effective alternative for the treatment of burn wounds in opossums, without causing adverse effects to the patient or her baby.
Lesão facial grave em um gambá-de-orelha-branca (Didelphis albiventris) - tratamento com ozonioterapia
Keywords: alternative therapies; healing; ozone therapy; tissue repair; wild animals